Novel use of interventional radiology in trauma - Jeph, Sunil; Ahmed, Saif; Bhatt, Ruchika Dua; Nadal, Luis L.; Bhanushali, Ashok (Journal of Emergency and Critical Care Medicine, 2017)
Trauma is one of the leading causes of mortality in the United States. There is a need for effective and efficient delivery of care that can improve survival and reduce morbidity as much as possible. Due to technological advances in interventional radiology (IR); there has been an expanding role for IR in hemodynamically stable and unstable patients. Various tools, such as micro catheters, stent grafts, digital subtraction angiography (DSA), and cone beam angiography have expanded the ability of the IR physician in reducing mortality and morbidity in patients who have suffered traumatic injuries. However, for the best possible patient care to be administered there must be two important resources readily available: the ability to triage before or quickly upon presentation to the hospital and a multidisciplinary trauma team which includes physicians and well trained ancillary staff. Here we describe the critical role IR plays in the trauma setting and its evolution and future growth, given the advances in technology.